Prevalence of dental anxiety and its associated factors among patients visiting tertiary care dental hospital in Kathmandu, Nepal: a cross-sectional study - Archana Shah; Krishna Subedi; Monika Kumal; Kanaklata Karn; Kiran Kandel; Alina Paneru (BMJ Open)
Background Dental anxiety, affecting 15.3% of adults globally, is more common in younger people and women. It often leads to avoiding dental visits, which worsens oral health. In Nepal, limited studies have focused on specific populations, leaving a gap in understanding its prevalence and associated factors among general dental outpatients.Objective This study aims to explore the prevalence of dental anxiety along with associated factors among patients visiting a tertiary care dental hospital.Design A cross-sectional design.Setting This study was conducted among outpatients visiting a tertiary care dental hospital in Kathmandu, Nepal, from July to October 2024. Dental anxiety was assessed using the Modified Dental Anxiety Scale-Nepali and a self-designed, semi-structured questionnaire that incorporated various demographic variables and the nature of the past and current dental visits. Data were entered in a Microsoft Excel sheet and analysed using SPSS V.27. Both descriptive and inferential findings were drawn from the study.Participants A total of 276 adult patients (18–65 years) participated in the study. Participants who can read and write the Nepalese language were included. Individuals with cognitive impairments, a diagnosed general anxiety disorder or those taking anxiolytic medications were excluded.Primary and secondary outcome measures Modified Dental Anxiety Scale (MDAS) scores and factors associated with dental anxiety.Results Prevalence of dental anxiety in the present study was found to be 47.82% (41.80% to 53.90%, 95% CI), which includes 44.8% (n=124) with moderate anxiety and 2.9% (n=8) with severe anxiety. The overall mean dental anxiety score on MDAS was 9.69±3.74. Significant differences in mean MDAS scores were observed in younger participants (18–30 years; p=0.01) and females (p=0.001). Additionally, those with no dental history and specific reasons for their current dental visit also showed significant differences in mean MDAS scores (p=0.049 and p=0.043, respectively).Conclusion Slightly more than two-fifths of the participants experienced moderate dental anxiety, while a smaller yet significant proportion experienced severe anxiety. It was found to be associated with factors such as age, sex, dental history and reason for current dental visit. These findings highlight the importance of further conducting large national-level studies and the need for targeted interventions by relevant stakeholders and researchers to develop effective patient management strategies, raise awareness through education and guide policymaking.